2010
DOI: 10.1002/jbm.a.32760
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight hyaluronic acid effects on murine macrophage nitric oxide production

Abstract: Hyaluronic acid (HA) is increasingly used for a number of medical device applications. Since the chemical structure of HA is identical no matter its bacterial or animal origin, it should be the ideal biomaterial. However, short term transient inflammatory reactions are common, while rare long-term adverse events may correlate with subclinical chronic inflammation. Concern has been raised that low molecular weight components or degradation fragments from implanted HA may directly stimulate inflammatory reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 89 publications
(154 reference statements)
3
52
0
Order By: Relevance
“…In this study, we demonstrate that LMW HA fragments do not bind or stimulate TLR2 or TLR4 on the cell surface, consistent with a recently published observation that LMW HA fragments are not TLR ligands (31). Applying LMW HA fragments to a murine macrophage cell RAW 264.7 failed to stimulate production of MIP-2, a classic proinflammatory cytokine, in agreement with previous reports that LMW HA did not stimulate production of IL-1b or NO (28,29).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, we demonstrate that LMW HA fragments do not bind or stimulate TLR2 or TLR4 on the cell surface, consistent with a recently published observation that LMW HA fragments are not TLR ligands (31). Applying LMW HA fragments to a murine macrophage cell RAW 264.7 failed to stimulate production of MIP-2, a classic proinflammatory cytokine, in agreement with previous reports that LMW HA did not stimulate production of IL-1b or NO (28,29).…”
Section: Discussionsupporting
confidence: 92%
“…1D). Our data are consistent with recent publications reporting that LMW HA does not stimulate chemokine production in the RAW 264.7 cell line, rat splenocytes, rat adherent differentiated primary macrophages, or primary human macrophages (28,29). rHuPH20 or LMW HA do not stimulate production of cytokines/chemokines in the air pouch model…”
Section: Lmw Ha Does Not Bind or Stimulate Tlr2 Or Tlr4supporting
confidence: 93%
See 2 more Smart Citations
“…However, there is no direct evidence that LMW HA binds to TLR2 or TLR4, and some reports have suggested that if endotoxin (a putative stimulator of inflammation) is reduced to extremely low levels in purified preparations, LMW HA does not trigger normal tissue macrophage-mediated inflammatory reactions [15,16]. Our research clearly demonstrates that endotoxin-free LMW HA fragments (molecular weight range: 5-500 kDa) do not bind either TLR2 or TLR4; nor do these fragments stimulate TLR2-or TLR4-mediated nuclear factor-kappa-B (NF-kB) pathway signaling [3].…”
Section: Contaminant Hypothesismentioning
confidence: 99%